Construction of solvent-dependent self-assembled porous Ni(ii)-coordinated frameworks as effective catalysts for chemical transformation of CO2. Issue 109 (11th November 2016) - Zhou, Zhen; Yang, Lu; Wang, Yefei; He, Cheng; Liu, Tao; Duan, Chunying
Abstract : Two types of Ni(ii )-based coordinated frameworks have been solvothermally synthesized via solvent driven self-assembly, showing efficient heterogeneous catalytic activity toward cycloaddition of CO2 with epoxides under ambient conditions. Abstract : Coordinated frameworks having large pores can accommodate organic molecules and adsorb gas, such as waste carbon dioxide, to transform into valuable chemical products. By incorporating a tetraphenylethylene moiety as the four-point connected node, herein, two types of Ni(ii )-based coordinated frameworks have been solvothermally synthesized via solvent driven self-assembly and structurally characterized. Notably, these two complexes both contain a trinuclear cluster but with different styles and construction modes. The IR and XRD spectra suggested that the two compounds are highly stable in various solvents, including water, DMF, C2 H5 OH, C2 H2 Cl2, DMSO and 1, 4-dioxane. Catalysis experiments indicated that both of them could act as effective heterogeneous catalysts for cycloaddition of CO2 with epoxides, forming cyclic carbonates under ambient conditions. Notably, the two catalysts contained the same amount of catalytic sites, but the activity ofNi-1 was significantly lower than that ofNi-2, demonstrating a size-selective catalytic performance.